Association between bariatric surgery with long-term analgesic prescription and all-cause mortality among patients with osteoarthritis: a general population-based cohort study. Issue 10 (October 2021) - Zeng, C.; Lane, N.E.; Li, X.; Wei, J.; Lyu, H.; Shao, M.; Lei, G.; Zhang, Y.
Summary: Objectives: There is still a large unmet need for novel osteoarthritis (OA) treatments that could provide clinically important effects on long-term pain relief (≥12 months). We examined the relation of bariatric surgery along with weight loss to analgesic prescription and all-cause mortality among individuals with OA. Methods: We conducted a cohort study among individuals with OA using The Health Improvement Network. We compared the rate of no analgesic prescription ≥12 consecutive months and the risk of all-cause mortality using inverse probability weighting Cox-proportional hazard models and the difference in number of analgesic prescriptions (non-steroidal anti-inflammatory drugs, opioids, and paracetamol) in the 50 th, 75 th and 90 th percentiles using quantile regression model between bariatric and non-bariatric cohorts. Results: Included were 588, 494 individuals (694 had bariatric surgery). Compared with non-bariatric group, the rate of no analgesic prescription ≥12 consecutive months was higher (HR = 1.23, 95% CI: 1.08–1.38) in bariatric surgery group, and the number of analgesic prescriptions was lower in the 75 th (44 vs 58) and 90 th (74 vs 106) percentiles during a mean follow-up of 4.3 years. All-cause mortality in bariatric surgery group was lower than comparison group (HR = 0.46, 95% CI: 0.41–0.51). Conclusion: This study presents the first evidence that bariatric surgery was associated with decreased long-term analgesic prescription and decreased all-cause mortality among individuals with OA. However, our findings may be overestimated owing to intractable confounding by indication for bariatric surgery; thus, future studies (e.g., clinical trials) are warranted.